Future health spending forecast in leading emerging BRICS markets in 2030: health policy implications - Mihajlo Jakovljevic; Demetrios Lamnisos; Ronny Westerman; Vijay Kumar Chattu; Arcadio Cerda (Health Research Policy and Systems, 2022)
The current research examines the decades-long underlying historical trends in BRICS countries' health spending and explores these data as the grounds for reliable forecasting of their health expenditures up to 2030.
Keywords: Border; Health; Indigenous; Indo-nepal; Tharu; Tribes